DYNAMIC LOAD LIFTING MECHANISMS IN COMPLEX RIG THE DESCENT-LIFTING OPERATIONS - Іващенко, Василь Трифонович; Лях, Михайло Михайлович; Витвицький, Василь Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper calculation of dynamic loads in the mechanisms of complex lifting rig while performing of descent - lifting operations during pidholennya drill string from the rotor is in the process of transferring the load from the table, hand on the rotor system and the tower. The analysis of oscillatory processes in complex mechanisms caused by inertial forces when lifting or lowering the drill string. Recommendations to reduce the dynamic loads in the lifting of the drilling rig.